The Wiley-Blackwell handbook of the treatment of childhood and adolescent anxiety - Essau, Cecilia; Ollendick, Thomas H. (Wiley, 2013)
This book presents a collection of readings from leading experts that reveal the most effective evidence-based interventions for the prevention and treatment of anxiety disorders in children and adolescents.